Avaliação da eficiência de comunicação em redes sociais digitais: uma análise exploratória do cenário de empresas no Brasil - Barcellos, Marco Antonio Rebelo (2010)
One of the key challenges facing marketers is to evaluate the results generated from the implementation of communication activities in companies. Through a survey of managers of companies using Social Networks in Brazil as a communication tool, have been identified: the practice of measuring the efficiency of communication in these enviroment; how to structure the actions of companies in the Social Networks; and the methods used to structure, measure and prioritize investments in this new digital world. As a result of the study, we identified that the level of business investment is considered low by managers and that, despite the low investment, companies have observed significant benefits for their business, resulting from activity with Social Networks. In a way, the managers interviewed believe that this tool is very recent and it should not bother to evaluate return on investments in Social Networks, at least for now, despite some concerns with corporate governance.